A study on the relationship between Malaysia outward foreign direct investment and U.S Dollar, Singapore Dollar and U.K Pound Sterling / Nik Dini Daziani Nik Derahman - Nik Derahman, Nik Dini Daziani (Faculty of Business and Management, 2007)
The study focuses on the relationship between me exchange rate (MYR/USO, MYR/SGD and MYR/E) with the Malaysia outflow foreign direct investment. The main purposes of this study Is to identify whether the independent variabIe. the exchange rate has a significant relationship with Malaysia outward foreign dired investment or not. The volatility of Malaysia outward foreign direct investmem from 1991 to 2006 has shown an unstable panem which inconsistently appreciated and sometimes depreciated. The secondary data collected for ‘his study consists of Malaysia outward foreign direct investment starting from the 1" quarter of 1991 to the 3’“ quarter of 2006. Meanwhile, the data for exchange rate is collected in monthly basis from year 1991 m 2006. However in order to standardize the data, it has been presented on quarterly basis. This study uses simple linear regression model to the data. Based on the analysis from simple linear regression, only MYR/USD and MYR/SGD have significant relationship which represents the Malaysia outward foreign direct investment, Meanwhile, UKI£ shows no significam rela‘ionship towards Malaysia outward foreign direct investment